Gene expression profile in metastatic and non-metastatic parathyroid carcinoma. Issue 2 (February 2021) - Condello, Vincenzo; Cetani, Filomena; Denaro, Maria; Torregrossa, Liborio; Pardi, Elena; Piaggi, Paolo; Borsari, Simona; Poma, Anello Marcello; Muscarella, Lucia Anna; Graziano, Paolo; Chiofalo, Maria Grazia; Repaci, Andrea; et al.
Abstract : Parathyroid carcinoma (PC) is one of the rarest and aggressive malignancies of the endocrine system. In some instances, the histological diagnosis remains uncertain unless there is evidence of gross local invasion or secondary spread. The identification of molecular markers could improve the diagnostic accuracy of these lesions. The expression of 740 genes involved in the tumor progression processes was assessed in 8 parathyroid adenomas (PAs), 17 non-metastatic and 10 metastatic PCs using NanoString technology. Clustering analysis and Ingenuity Pathway Analysis (IPA) were interrogated to compare the gene expression profiles among the three analyzed groups and to evaluate the potential role of differentially expressed genes, respectively. The 103 differentially expressed genes between metastatic PCs and PAs are able to discriminate perfectly the two groups from a molecular point of view. The molecular signatures identified in non-metastatic PCs vs PAs and in metastatic PCs vs non-metastatic PCs comparisons, although with some exceptions, seem to be histotype-specific IPA reveals that hepatic fibrosis/hepatic stellate cell activation and GP6 signaling pathway are involved in malignant behavior of parathyroid tumors, whereas the activation of the HOTAIR regulatory pathway are involved in the metastatization process. Our investigation identified differentially expressed genes in non-metastatic PCs mainly encoding ECM proteins and in metastatic PCs driving endothelial-to-mesenchymal transition or encoding mediators of angiogenesis. The identified genes might be promising molecular markers potentially useful in the clinical practice for the early diagnosis and prognosis of PC.